The Research On Management Power, Executive Compensation, And Corporate Value Of Chinese-Listed Companies - Li , Baochan; Pongtornkulpanich, Anan; Chankoson, Thitinan (Migration Letters, 2024)
In this study, the purpose is that as trustees of the owners, senior management personnel control enterprise resource allocation and make significant decisions. Implementing effective power allocation mechanisms for management personnel and incentive systems for executive compensation can enhance enterprise value. This paper aims to investigate the interconnections between management power and executive compensation, executive compensation and corporate value, management power and corporate value, as well as the potential mediating impact of executive compensation on the relationship between management power and corporate value. The research design involves an empirical study conducted using data collected from Chinese-listed companies spanning the years 2013 to 2022. The relationships between management power, executive compensation, and corporate value were empirically examined through literature research, principal component analysis, and multiple linear regression methods. The empirical results indicate that increasing management power can lead to elevated executive compensation, subsequently enhancing corporate value. Furthermore, executive compensation exhibits a significantly positive influence on corporate value, and it functions as a mediator between management power and corporate value in the current Chinese context. The research limitations include that the study did not analyze the impact of the power held by independent directors and other entities on enterprise value within the measurement of management power. Additionally, the measurement of executive compensation did not encompass non-monetary benefits. The practical implications suggest that management power positively affects executive compensation, and executive compensation operates as a mediator between management power and corporate value. Consequently, endowing management with appropriate power and designing a rational executive compensation system can effectively enhance corporate value. The research’s value lies in the empirical findings that highlight the mediating role of executive compensation between management power and corporate value. These results provide empirical insights into the control of management power and executive compensation, offering guidance for effectively managing these aspects.